Aberrant subcutaneous adipogenesis precedes adult metabolic dysfunction in an ovine model of polycystic ovary syndrome (PCOS). (1st January 2021) - Siemienowicz, Katarzyna J.; Coukan, Flavien; Franks, Stephen; Rae, Mick T.; Duncan, W. Colin
Abstract: Polycystic ovary syndrome (PCOS) affects over 10% of women. Insulin resistance, elevated free fatty acids (FFAs) and increased adiposity are key factors contributing to metabolic dysfunction in PCOS. We hypothesised that aberrant adipogenesis during adolescence, and downstream metabolic perturbations, contributes to the metabolic phenotype of adult PCOS. We used prenatally androgenised (PA) sheep as a clinically realistic model of PCOS. During adolescence, but not during fetal or early life of PA sheep, adipogenesis was decreased in subcutaneous adipose tissue (SAT) accompanied by decreased leptin, adiponectin, and increased FFAs. In adulthood, PA sheep developed adipocyte hypertrophy in SAT paralleled by increased expression of inflammatory markers, elevated FFAs and increased expression of genes linked to fat accumulation in visceral adipose tissue. This study provides better understanding into the pathophysiology of PCOS from puberty to adulthood and identifies opportunity for early clinical intervention to normalise adipogenesis and ameliorate the metabolic phenotype. Graphical abstract: Image 1 Highlights: Prenatal androgenization of female sheep is a model of Polycystic Ovary Syndrome. In adolescence, these sheep have reduced adipogenesis in subcutaneous fat. This is linked with reduced adiponectin, decreased storage capacity and fatty liver. In adulthood, these sheep have subcutaneous adipocyte hypertrophy and inflammation. In adulthood, fat storage promoting genes are upregulated in visceral fat.